Institutional reforms debate and FDI flows to MENA region: Does one 'best' fit all? - Wasseem Michel Mina (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
The paper revisits the policy debate on institutional reform approaches to property rights protection and empirically examines it in the context of FDI flows to the Middle East and Northern Africa region (MENA).Using panel data on 11 MENA countries for the period 1991-2007 and adopting feasible generalized least squares estimation methodology, the paper finds a positive influence of improvement in the risk of investment expropriationin non-Gulf Cooperation Council (GCC) MENA countries and of bilateral investment treaties (BITs) in GCC countries. The joint influence of domestic institutional functions and BITs is positive in specifications containing investment expropriation risk and government stability in non-GCC MENA countries, and corruption in GCC countries. Results have important policy implications for the institutional reform approach to be adopted.
Keywords: F21; K33; O16; O17; O19; 330; property rights protection; bilateral investment treaties; foreign direct investment; institutional reforms; MENA; heterogeneity; Direktinvestition; Eigentumsrecht; Investitionsgarantie; MENA-Staaten